Searching for keystone plant resources in fruit‐frugivore interaction networks across the Neotropics - Messeder, João Vitor S.; Guerra, Tadeu J.; Dáttilo, Wesley; Silveira, Fernando A. O. (Biotropica, 2020)
Identifying keystone plant resources (KPR) is a contentious issue in ecology and conservation. Despite recent advances provided by mutualistic networks, we still lack studies addressing large‐scale identification of keystone plants. We developed a novel quantitative framework for the large‐scale identification of KPR that combines centrality and effects of simulated removals on networks properties. We built a database with 38 fruit–frugivore networks comprising 6,180 pairwise interactions from Neotropical forest and non‐forest ecosystems ranging from sea level to 2,500 m a.s.l.. Effects of random removal simulations and removal of keystone taxa candidates on nestedness, modularity and niche overlap were assessed. Furthermore, we tested whether changes in network descriptors responded to both latitudinal and elevational gradients. From a total of 373 genera on networks, only species in six genera were ranked as keystone candidates. The simulated removal of species in Miconia (Melastomataceae), Cecropia (Urticaceae) and Byrsonima (Malpighiaceae) led to significant changes in nestedness, modularity and niche overlap, suggesting that these plants play important roles in maintaining the structure of Neotropical fruit–frugivore interaction networks, regardless of latitude or elevation. Our results confirm the keystone role of previously recognized taxa, recognize overlooked ones, providing support for their role at a biogeographical scale, and partially challenge taxa traditionally identified as keystone resources for frugivores. Our study has implications for conservation and restoration of Neotropical ecosystems and provides a new framework for large‐scale identification of keystones in other types of ecological networks. in Spanish is available with online material. RESUMEN Identificar los recursos clave (KPR) es un tema polémico en ecología y conservación. A pesar de los recientes avances proporcionados por las redes mutualistas, todavía carecemos de estudios que aborden la identificación a gran escala de plantas clave. Desarrollamos un nuevo marco de trabajo cuantitativo para la identificación a gran escala de KPR que combina la centralidad y los efectos de las eliminaciones simuladas en las propiedades de las redes. Construimos una base de datos con 38 redes fruto‐frugívoro que comprenden 6,180 interacciones por pares en ecosistemas Neotropicales, forestales y no forestales, que van desde el nivel del mar hasta los 2.500 m a.s.l.. Los efectos de las simulaciones aleatorias de remoción y la eliminación de taxa claves en anidamiento, modularidad y superposición de nichos fueron evaluados. Además, probamos si los cambios en los descriptores de red respondían a los gradientes latitudinales y de elevación. De un total de 373 géneros en las redes, solo las especies en seis géneros se clasificaron como recursos claves potenciales. La eliminación simulada de especies en Miconia (Melastomataceae), Cecropia (Urticaceae) y Byrsonima (Malpighiaceae) ha causado cambios significativos en anidamiento, modularidad y superposición de nichos, lo que sugiere que estas plantas desempeñan un papel importante en el mantenimiento de la estructura de las redes de interacción Neotropicales de fruto‐frugívoros, independientemente de la latitud o la elevación. Nuestros resultados confirman el papel clave de los taxon previamente reconocidos, reconocen los que se pasan por alto, brindan apoyo para su papel a escala biogeográfica, y desafían parcialmente los taxon tradicionalmente identificados como recursos clave para los frugívoros. Nuestro estudio tiene implicaciones para la conservación y restauración de los ecosistemas Neotropicales y proporciona un nuevo marco de trabajo para la identificación a gran escala de las especies claves en cualquier tipo de redes ecológicas.